METTL3-dependent m6A RNA methylation suppresses aberrant mammary epithelial differentiation and neoplastic transformation - Yihao Li; Xintao Qiu; Zachary Sandusky; Kaitlin Tagliaferri; Rong Li; Xin Yang; Tao Zhang; Shimeng Liu; Pengze Yan; Feng Lu; Marcus Jones; Tengfei Xiao; et al. (Proceedings of the National Academy of Sciences, 2025)
The mechanisms underlying sustained proliferation and aberrant cellular plasticity that drive early breast tumorigenesis remain unclear. Using CRISPR knockout (KO) screens, we systematically characterized the regulators of cellular fitness in the normal mammary epithelium. We found that loss of METTL3 stimulates mammary epithelial proliferation and reprograms gene expression in an m6A methyltransferase-dependent manner. Single-cell analysis in normal breast organoids revealed that METTL3 ablation causes disruption of the mammary cellular hierarchy through increased aberrant luminal differentiation. Mechanistically, METTL3 loss reduces RNA m6A modification of transcribed transposable elements leading to their increased expression and upregulation of interferon-STAT signaling. This inflammatory response leads to cross talk between STAT and GATA3 transcription factors, resulting in transcriptional activation of luminal genes in the mammary epithelium. These findings identify a cell-intrinsic epigenetic loop contributing to mammary epithelial differentiation and highlight a potential role of loss of METTL3-dependent m6A modification during neoplastic transformation.